On the Approach to the Object of Study from the Perspective of the Contrary Concept of the True - Hakobyan, Gevorg (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
Article discusses some difficulties related with the process of differentiation of mental structures, and emphasizes that no matter what gnoseological qualities they receive, in the end it is necessary to find out whether they are true or not. However, it finds out that due to the impossibility of defining and making precise the concept of true, the process of differentiation gets into a paradoxical situation and faces an insurmountable barrier. Therefore, instead of overcoming the barrier, it is proposed to bypass it and implement the differentiation of mental structures from the racurce of the contrary concept of the true, which, although again very problematic, nevertheless is a completely feasible process of the recognition.